Microbiological investigation and determination of the antimicrobial potential of cow dung samples (Stamford Journal of Microbiology, 2019)
Cow dung is being used in agriculture as well for the household and religious purposes from the ancient time. Cow dung is known to possess antimicrobial activity and contains a wide variety of microorganisms with variable properties. Therefore, the present study was carried out to assess the microbial diversity including pathogenic ones of the cow dung samples as well as to determine the antimicrobial traits of the samples. In this regard, a total of 8 fresh cow dung samples were tested. All the samples contained a huge load of bacteria and fungi in an average of 108 and 107 cfu/g, respectively. An extended number of pathogenic bacteria were recovered. Among the pathogenic bacteria, Staphylococcus spp. and Bacillus spp. were predominantly found in every sample. The presence of Pseudomonas spp. Escherichia coli, Klebsiella spp. and fecal coliform were exhibited in most of the samples. Salmonella spp. and Vibrio spp. were found in 3 and 5 samples, respectively. The average load of the pathogens was 104 cfu/g. All the samples showed substantial degree of antimicrobial activity against all the pathogens tested. Samples 1, 2, 3 and 4 were effective in inhibiting the growth of all the tested pathogens. The findings of the present study revealed the need for safe application of cow dung in the agricultural field and of further investigation for the antimicrobial potential of the diversified microflora of cow dung offering agricultural, environmental and medical applications.Stamford Journal of Microbiology, Vol.8(1) 2018: 34-37